(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
End-stage chronic kidney disease (CKD) has been one of the most pressing medical problems of the last decade. The relevance of the topic reflects the high cost of socio-medical problems, the fact that not all patients participate in program hemodialysis, as well as the fact that the number of patients requiring hemodialysis is increasing four times a year. In developed countries, end-stage CKD is steadily increasing, and elderly patients over 55 years of age have a share of the risk of death.